Sanitary-epidemiological legislation in the ukrainian provinces in the early twentieth century - Гоцуляк, С. Л. (Problems of legality, 2014)
The article is devoted to the sanitary and epidemiological legislation rescard in the early twentieth century. The analysis of legislation is illuminated in terms of its completeness and clarity. The makes the conclusions that the proper sanitary and epidemic legal regulation can protect the population from infective diseases.